Professional Accounting Regulation in the Kingdom of Thailand over the Past Fifty Years - Pholkaew, Chaimongkol; Yapa, Prem (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2017)
The purpose of this study is to explore the development of the professional accounting regulation and the accounting profession in the Kingdom of Thailand over the past fifty years. The development of Thailand’s accounting profession was independent and uninfluenced by Western colonial powers compared to most of its neighboring countries. This distinct situation is the motivation for this study. This study used in-depth interview as means of collecting data from accountants, auditors, academic professionals, and representatives from the Ministry of Commerce and Ministry of Finance. The findings showed that the state played a significant role in the emergence and development of the accounting profession in its early years through the enactment of accounting laws and regulations. The accounting profession is not an autonomous organization as in western countries due to state dominance by the establishment of state agencies. However, developments of the accounting profession from 2004 onwards indicate that the interaction among various factors such as professional accounting regulation, globalization, politico-economic milieu, and educational institutions accelerates the development of the accounting profession.